2012
DOI: 10.1007/s00128-012-0564-4
|View full text |Cite
|
Sign up to set email alerts
|

Metals in the Tissues of Two Fish Species from the Rare and Endemic Fish Nature Reserve in the Upper Reaches of the Yangtze River, China

Abstract: Concentrations of copper, zinc, mercury, and arsenic were measured in the muscle, gill and liver tissues of Coreius heterodon and Pelteobagrus vachelli collected from the rare and endemic fish nature reserve in the upper reaches of the Yangtze River. The concentrations of copper and zinc in the tissues of these two fish species were higher than those of mercury and arsenic. Highest metal concentrations were generally found in fish samples from Yibin. The concentrations of copper, zinc, mercury, and arsenic in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…The high concentrations of Zn, Fe and Cu in A. latus may attribute to the accumulation of these metals from the industrial and domestic wastewater discharges. This support the earlier evidences of Demirak et al (2006), Shenwen et al (2012) and Jean et al (2013). Parts-wise analysis showed variations in the mean concentrations of metals in the muscle, liver and gills of A. latus which may be related to the differences in ecological requisites, (Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The high concentrations of Zn, Fe and Cu in A. latus may attribute to the accumulation of these metals from the industrial and domestic wastewater discharges. This support the earlier evidences of Demirak et al (2006), Shenwen et al (2012) and Jean et al (2013). Parts-wise analysis showed variations in the mean concentrations of metals in the muscle, liver and gills of A. latus which may be related to the differences in ecological requisites, (Fig.…”
Section: Resultssupporting
confidence: 92%
“…When these pollutants containing trace metals reach beyond the threshold limits, they become toxic to the marine organisms and the surrounding environment. Coastal or Bay dwelling demersal commercial fishes in 'stressed' marine environment revealed high trace metals levels due to their life history characteristics and accumulation of pollutants from sediment and possible anthropogenic sources than the metals levels in pelagic, deep-sea and migratory fishes (Shenwen et al 2012;Asante et al 2010;Roach et al 2008;Demirak et al 2006;Mormede and Davies 2001). This directed our studies to determine the trace metals pollution in wastewater and also in Acanthopagrus latus fish observed near the wastewater drain outlet mouth.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (2011) reported changes in fish assemblages following the completion of TGD. Other studies focused on the reproduction of major commercially important fish such as the major Chinese carp Hu et al 2014) or endangered species (Chen et al 2011;Zhang et al 2014) while some studies focused on heavy metal accumulation (Cai et al 2012;Yi and Zhang 2012) or conservation biology Ye et al 2014). There is a severe lack of research work on trophic ecology of fish related to the TGD construction.…”
Section: Introductionmentioning
confidence: 99%
“…A thorough search of the literature showed that Hg data for fish before and after the impoundment are only available for three species [41][42][43][44][45]: bronze gudgeon (Coreius heterodon), common carp (Cyprinus carpio) and Amur catfish (Silurus asotus). Although the data are not corrected for fish age, the sizes and weights collected in these studies seemed to be comparable.…”
Section: Implications For the Three Gorges Reservoirmentioning
confidence: 99%
“…Yu et al [45] further noted that after the impoundment, higher increase was observed in muscle Hg concentrations in fish species that are at higher trophic levels and inhabit in deeper waters. A recent study found that the Hg concentrations in the muscle of bronze gudgeon from Yibin and Banan in the upper reaches of Yangtze Rive and in darkbarbel catfish (Pelteobagrus vachelli) from Yibin have exceeded the safe limit level (300 ng/g ww) for human consumption [44]. This is alarming as both are important commercial and edible fish in the region.…”
Section: Implications For the Three Gorges Reservoirmentioning
confidence: 99%